Outcomes of Cranioplasty Using Autologous Bone or 3D-Customized Titanium Mesh Following Decompressive Craniectomy for Traumatic Brain Injury: Differences in Complications - Junwon Kim; Jang Hun Kim; Jong Hyun Kim; Taek-Hyun Kwon; Haewon Roh (Journal of Trauma and Injury)
Purpose Cranioplasty (CP) is often required for survival after decompressive craniectomy. Several materials, including autologous bone and various artificial materials, have been introduced for CP, but it remains unclear which material is best for CP. This study aimed to explore differences in complications between patients who underwent CP using an autologous bone flap versus a three-dimensional (3D) titanium mesh and to identify significant risk factors for post-CP complications. Methods In total, 44 patients were enrolled in this study and divided into two groups (autologous bone vs. 3D titanium mesh). In both groups, various post-CP complications were evaluated. Through a comparative analysis, we aimed to identify differences in complications between the two groups and, using binary logistic analysis, to determine significant factors associated with complications after CP. Results In the autologous bone flap group, there were three cases of surgical infection (3/24, 12.5%) and 11 cases of bone flap resorption (BFR) (11/24, 45.83%). In the 3D titanium mesh group, there was only one case of surgical infection (1/20, 5%) and 11 cases of various complications, including mainly cosmetic issues (11/20, 55%). A subgroup risk factor analysis of CP with an autologous bone flap showed no risk factors that predicted BFR with statistical significance, although a marginal association was found between larger bone flaps and BFR (odds ratio [OR]=1.037, p=0.090). In patients treated with a 3D titanium mesh, multivariate analysis revealed that only the existence of a ventriculo-peritoneal shunt system was strongly associated with overall post-CP complications (OR=18.66, p=0.021). Conclusions Depending on which material was used, different complications could occur, and the rate of complications was relatively high in both groups. Hence, the material selected for CP should be selected based on individual patients’ conditions.